Sex, lies, & brain scans: how fMRI reveals what really goes on in our minds - Sahakian, B. J. (Oxford University Press, 2017)
'Sex, lies, & brain scans' takes readers beyond the media headlines. Barbara Sahakian and Julia Gottwald consider what the technique of fMRI entails, and what information it can give us, showing which applications are possible today, and which ones are science fiction. They also consider the important ethical questions these techniques raise. Should individuals applying for jobs as teachers or judges be screened for unconscious racial bias? What if the manipulation of love using 'love potions' was misused for economic or military ends? How far will we allow neuroscience to go? It is time to make up our minds. --